Rethinking Coastal Waste: Integrating Green Criminology and Community Engagement for Sustainable Solutions - Fenty Puluhulawa; Amanda Adelina Harun; Moh. Rusdiyanto Puluhulawa; Sherly Joice Pangayow; Karlin Z Mamu (Faculty of Law, Universitas Sebelas Maret, 2025)
Fisheries, tourism, and transportation depend on coastal habitats, which support diverse wildlife. Plastic garbage increasingly endangers these areas, which harms marine life and the ecology. This study examines how coastal garbage management affects legal knowledge, compliance behaviour, and community participation. The study uses green criminology to show how conventional legal systems prioritise direct crimes over environmental crimes, such as inappropriate plastic and waste disposal. The study found a large difference between coastal communities' environmental knowledge and compliance. Despite knowing the rules, many community members break them due to a lack of enforcement, infrastructure, or motivation. This circumstance emphasises the need for stronger laws, greater enforcement, and more inclusive community-based trash management. Sustainable coastal management requires community involvement and legal accountability to protect ecosystems and public health